ASSOCIATION BETWEEN AQUEOUS HUMOR CXC MOTIF CHEMOKINE LIGAND 13 LEVELS AND SUBFOVEAL CHOROIDAL THICKNESS IN NORMAL OLDER SUBJECTS. Issue 1 (January 2016) - Nomura, Yoko; Takahashi, Hidenori; Fujino, Yujiro; Kawashima, Hidetoshi; Yanagi, Yasuo
Abstract : Purpose: To investigate the association of subfoveal choroidal thickness with intraocular inflammatory cytokines and chemokines. Methods: The subjects consisted of 76 eyes of consecutive cataract patients at the Japan Community Health Care Organization Tokyo Shinjuku Medical Center between September 2010 and August 2012. In addition, two autopsy eyes from elderly males were used for immunohistochemical study. Subfoveal choroidal thickness was measured using spectral domain optical coherence tomography before cataract surgery. At the beginning of cataract surgery, a sample of undiluted aqueous humor was manually aspirated and the concentrations of the following cytokines were determined using a multiplex cytokine assay: IP-10, MCP-1, MMP-9, IL-6, IL-10, CXCL1, CXCL12, CXCL13, and CCL11. The association of subfoveal choroidal thickness with intraocular cytokine concentration was analyzed. Expression of CXCL13 was examined in autopsy eyes. Results: Among these factors, higher concentration of CXCL13 was associated with thicker choroid. In particular, multiple regression analysis showed that the concentration of CXCL13 was associated with subfoveal choroidal thickness ( P = 0.001), independently of axial length ( P = 0.049). By immunostaining, CXCL13 was clearly detected in choroidal endothelial cells. Conclusion: Aqueous humor concentration of CXCL13 is correlated with subfoveal choroidal thickness in normal subjects. Abstract : This prospective study revealed that the concentration of CXCL13 in the aqueous humor is correlated with subfoveal choroidal thickness in normal subjects. By immunostaining, CXCL13 was clearly detected in choroidal endothelial cells in autopsy eyes. CXCL13 is worthy of note when choroid is investigated in further studies.